1989
DOI: 10.1073/pnas.86.16.6393
|View full text |Cite
|
Sign up to set email alerts
|

Selective changes in mu opioid receptor properties induced by chronic morphine exposure.

Abstract: Chronic infusion of morphine to guinea pigs produced selective changes in Im agonist binding properties in cerebrocortical membrane preparations. Employing the pselective opioid agonist MePhe4, in direct binding studies and in competition of labeled antagonist binding, we found that the major changes were a decrease in the number of sites with high affnity for agonist, a small reduction in total receptor number, and a loss in the ability of guanosine 5'-[y-thio]triphosphate to regulate binding. A fraction of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
38
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(42 citation statements)
references
References 19 publications
3
38
1
Order By: Relevance
“…In the present study, we clearly show that chronic morphine produces a significant upregulation rather than downregulation of -opioid receptors in vivo under conditions that induce profound cellular tolerance. This is in contrast to the majority of previous binding studies, which detected no change in functional -opioid receptor binding sites in morphine-tolerant mice (Law et al, 1983;Werling et al, 1989). Given that morphine blocks receptor internalization, it is possible that in the continuous presence of morphine nonfunctional mice were treated with the indicated doses of morphine or fentanyl.…”
Section: Discussioncontrasting
confidence: 52%
“…In the present study, we clearly show that chronic morphine produces a significant upregulation rather than downregulation of -opioid receptors in vivo under conditions that induce profound cellular tolerance. This is in contrast to the majority of previous binding studies, which detected no change in functional -opioid receptor binding sites in morphine-tolerant mice (Law et al, 1983;Werling et al, 1989). Given that morphine blocks receptor internalization, it is possible that in the continuous presence of morphine nonfunctional mice were treated with the indicated doses of morphine or fentanyl.…”
Section: Discussioncontrasting
confidence: 52%
“…The effects of chronic morphine administration on MOP binding site density have also been investigated in animal brain and brain regions. These studies produced all possible changes in MOP density, namely, up-regulation (Besse et al, 1992;Brady et al, 1989;Fabian et al, 2002;Fabian et al, 2003;Holaday et al, 1982;Ray et al, 2004;Rothman et al, 1991;Schmidt et al, 2003;Vigano et al, 2003), down-regulation (Bhargava and Gulati, 1990;Meuser et al, 2003;Werling et al, 1989) or no change (Polastron et al, 1994;Stafford et al, 2001;Turchan et al, 1999). Some of these results appear to be regional differences, but others, performed on whole brain or the same regions of the same animal, appear to be discrepancies between different laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…While the full description of each of these components will ultimately be required to understand the consequences of prolonged opioid exposure, the recent cloning of the ,a-, 6-, and K-opioid receptors (see Kieffer, 1995) has opened up the study of the molecular basis of opioid desensitization of the signaling process. Several studies have shown that opioid receptors desensitize by uncoupling from their G protein (Werling et al, 1989;Tao et al, 1993), and opioid agonist efficacy is reduced during the development of tolerance Goldstein, 1982, 1984;Porreca and Burks, 1983).…”
mentioning
confidence: 99%